Information-seeking behaviour: A case study on farmers in Maputo City, Mozambique - Mabuie, Maltez Alberto; Siueia Júnior, Matias; Monjane Mabuie, Artimísia Jaime (Technium Social Sciences Journal, 2020)
In the agricultural sector, which is a pillar for the development of the world economy, and for family subsistence, having information is critical. The objective of this study is to analyse the information-seeking behaviour of farmers in Maputo City, Mozambique. A case study was conducted involving ten farmers from the KaMbukwana and KaMovata Municipal Districts. For the practice of agriculture, farmers in Maputo City largely depend on information from their fellow farmers and on government institutions as a reliable source. Other sources of information include television, workshops and non-governmental organisations. There is a high perception of relevancy of information for practice of agriculture; the farmers appeal for the use of information and communications technology as a mechanism to share information.